Fault-Tolerant Control for N-Link Robot Manipulator via Adaptive Nonsingular Terminal Sliding Mode Control Technology. (6th July 2021) - Shi, Nannan; Luo, Fanghui; Kang, Zhikuan; Wang, Lihui; Zhao, Zhuo; Meng, Qiang; Hou, Weiqin
Abstract : An adaptive nonsingular terminal sliding mode control (ANTSMC) scheme for the n -link robot manipulator is presented in this study, which can achieve faster convergence and higher precision tracking compared with the linear hyperplane-based sliding mode control. Novel adaptive updating laws based on the actual tracking error are employed to online adjust the upper bound of uncertainty, which comprehensively consider both the tracking performance and chattering eliminating problem. The stability analysis of the proposed ANTSMC is verified using the Lyapunov method with the existence of the parameter uncertainty and the actuator faults. Numerical simulation studies the comparison of performance between ANTSMC and the conventional nonsingular terminal sliding mode control (NTSMC) scheme to validate the advantages of the proposed control algorithm.